Sweden : Financial Sector Assessment Program Update-Detailed Assessment of Observance on Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2011)
The staff report highlights that the insurance sector in Sweden is well developed and mature. The captive insurance segment is mainly driven by tax advantages. This assessment provides an update on the significant regulatory and supervisory developments in the insurance sector of Sweden since 2002. The assessment is based solely on the laws, regulations, and other supervisory requirements and practices that were in place at the time of the assessment.